Identifying predictors of delayed diagnoses in symptomatic breast cancer: a scoping review. (7th March 2016) - Webber, Colleen; Jiang, Li; Grunfeld, Eva; Groome, Patti A.
Abstract : Delayed diagnosis of breast cancer can adversely impact patient outcomes. To better understand this issue, we conducted a scoping review of literature from 1996 to 2015 that examined predictors of delayed presentation and diagnosis among women with breast cancer symptoms. We performed searches to identify studies of predictors of the time from symptom onset to first presentation (the patient interval), first presentation to diagnosis (the diagnostic interval) and symptom onset to diagnosis (the total interval) among women with breast cancer symptoms. Two reviewers independently reviewed and abstracted the findings of these studies. Of the 22 studies included in this review, 16 examined predictors of the patient interval, six examined predictors of the diagnostic interval and four examined predictors of the total interval. A total of 116 predictors were examined; three had evidence of an association with a less timely diagnosis: not disclosing symptoms to others, non‐lump breast symptoms and African American ethnicity. Improving awareness of atypical breast cancer symptoms and encouraging disclosure could improve the timeliness of a breast cancer diagnosis. Access concerns for vulnerable groups need to be addressed. Future research should be more purposeful in its choice of predictors, possibly through the use of established conceptual frameworks.